(untitled) (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study is to determine the influence between Integrated Entrepreneurship Education (IEE) and Multidimensional Poverty Alleviation (MPA), Integrated Entrepreneurship Education (IEE) and Entrepreneurial Intention (EI), Entrepreneurial Intention (EI) and Multidimensional Poverty Alleviation (MPA), Integrated Entrepreneurship Education (IEE), Multidimensional Poverty Alleviation (MPA) and Entrepreneurial Intention (EI)